2020
DOI: 10.1515/revneuro-2020-0023
|View full text |Cite
|
Sign up to set email alerts
|

The biological and diagnostic roles of MicroRNAs in meningiomas

Abstract: MicroRNAs (miRNAs) refer to a class of small endogenous non-coding RNAs that regulate gene expression at the post-transcriptional level. Emerging studies have shown that miRNAs play critical roles in tumorigenesis and cancer progression. However, roles and mechanisms of miRNA dysregulation in the pathogenesis of meningioma are not fully understood. Here, we first reviewed existing research of aberrantly expressed miRNAs identified by high throughput microarray profiling in meningioma. We also explored the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…In meningiomas, microRNA biomarkers in serum could be developed as a convenient and effective indicator to diagnose and monitor meningioma's; our results demonstrate that miR-181d is a promising candidate. Little studies have demonstrated a plasmatic profile of microRNA expression in patients with meningiomas, evidencing eventual usefulness for tracking and monitoring these patients [23,24] Lakomy et al [25] analyzed 38 samples of patients diagnosed with glioblastomas who presented 32% methylation of MGMT by real-time PCR. High expression of miR-21 and miR-181c was also observed, and this high expression was associated with early progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In meningiomas, microRNA biomarkers in serum could be developed as a convenient and effective indicator to diagnose and monitor meningioma's; our results demonstrate that miR-181d is a promising candidate. Little studies have demonstrated a plasmatic profile of microRNA expression in patients with meningiomas, evidencing eventual usefulness for tracking and monitoring these patients [23,24] Lakomy et al [25] analyzed 38 samples of patients diagnosed with glioblastomas who presented 32% methylation of MGMT by real-time PCR. High expression of miR-21 and miR-181c was also observed, and this high expression was associated with early progression.…”
Section: Discussionmentioning
confidence: 99%
“…In meningiomas, microRNA biomarkers in serum could be developed as a convenient and effective indicator to diagnose and monitor meningioma’s; our results demonstrate that miR-181d is a promising candidate. Little studies have demonstrated a plasmatic profile of microRNA expression in patients with meningiomas, evidencing eventual usefulness for tracking and monitoring these patients [ 23 , 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the miRNA regulatory network is far-reaching [21]. Previous studies have veri ed that miRNAs are important small regulatory ncRNA molecules that control a fairly large number of biological processes; their important functions have generated interest in their use as biomarkers and their roles as regulators of ageing [21,60] and a number of cancer types [61][62][63]. Recent studies have also suggested that miRNAs are involved in the regulation of age-associated processes and pathologies in multiple mammalian tissues, including the brain, heart, bones, and muscles [21,[64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, a higher requirement for clinical management is warranted. It is well documented that the best way to improve the prognosis of brain tumor patients is via total tumor resection [ 2 ]. However, tumors at advanced stages or malignant tumors could be challenging to excise.…”
Section: Introductionmentioning
confidence: 99%